Diseased-induced multifaceted variations in community assembly and functions of plant-associated microbiomes - Kuang, Lu; Li, Ting; Wang, Baozhan; Peng, Junwei; Li, Jiangang; Li, Pengfa; Jiang, Jiandong (Frontiers in Microbiology, 2023)
Plant-associated microorganisms are believed to be part of the so-called extended plant phenotypes, affecting plant growth and health. Understanding how plant-associated microorganisms respond to pathogen invasion is crucial to controlling plant diseases through microbiome manipulation. In this study, healthy and diseased (bacterial wilt disease, BWD) tomato (Solanum lycopersicum L.) plants were harvested, and variations in the rhizosphere and root endosphere microbial communities were subsequently investigated using amplicon and shotgun metagenome sequencing. BWD led to a significant increase in rhizosphere bacterial diversity in the rhizosphere but reduced bacterial diversity in the root endosphere. The ecological null model indicated that BWD enhanced the bacterial deterministic processes in both the rhizosphere and root endosphere. Network analysis showed that microbial co-occurrence complexity was increased in BWD-infected plants. Moreover, higher universal ecological dynamics of microbial communities were observed in the diseased rhizosphere. Metagenomic analysis revealed the enrichment of more functional gene pathways in the infected rhizosphere. More importantly, when tomato plants were infected with BWD, some plant-harmful pathways such as quorum sensing were significantly enriched, while some plant-beneficial pathways such as streptomycin biosynthesis were depleted. These findings broaden the understanding of plant–microbiome interactions and provide new clues to the underlying mechanism behind the interaction between the plant microbiome and BWD.